Peran Orang Tua sebagai Pendamping Belajar Siswa di SDN Cimanuk 3 - Agustin, Rini; Kuntari, Septi (YASIN, 2022)
This study aims to determine the analysis of the role of parents in assisting student learning at SDN Cimanuk 3. This research is a qualitative research with a case study approach. The participants of this study were the parents of 2rd grade students of SDN Cimanuk 3 as many as 3 parents and guardians of students. This study uses data collection methods in the form of observation, interviews and documentation. The results of the study indicate that the role of parents has a very important role in the process of assisting children's learning, such as providing correct direction to children, support, and providing solutions to children's problems during learning, besides the attention and affection of parents can make encouragement in learning. motivate children's learning. If the child is able to feel the attention and affection of his parents, then the child will feel more comfortable and will be obedient to his parents and will give good things in the learning process and improve children's learning achievement.